Pengelolaan Karakter Kerja Keras Dalam Ekstrakurikuler Pramuka Di SD N 1 Plosorejo - Kusumaningtyas, Wahyu, Prof. Dr. Sutama, M.Pd, Dr. Sabar Narimo, MM, M.Pd (2016)
This study aimed to describe the character of the management of hard work in the scout -based extracurricular exemplary and habituation and to describe the constraints arising from the management of hard work in the character of SD Negeri 1 Plosorejo. This research is qualitative. Data collection techniques with interviews, observation, and documentation.Data analysis techniques to the analysis of the site.The process of collecting data through data reduction, data presentation, and conclusion.The validity of test data using kredibility, transferability test, certainty test, and dependence test. The results of this study are: (1) The values of scouting sourced from Tri Satya, Dharma Dasa, competency and skill held by members of the scout. Hard working character who wants to be transmitted to the students, must begin by example given by principals and teachers, including the implementation of extracurricular activities scouts. (2) Habituation characters hard work in extracurricular activities scouts in students by providing an activity that requires each individual doing his job alone though such activity is a unity that can not stand alone. (3) Inhibiting factors encountered in the management of characters hard work in implementing extracurricular scout at SDN 1 Plosorejo situated on technical factors where this activity is carried out in the afternoon were largely used students to rest, play and to recite, other technical factors are when entry the rainy season many students who do not set out to follow the scouts extracurricular activities, this causes maximal activity. Besides the lack of equipment and detailed material for field activities is also a limiting factor in extracurricular activities in SD N 1 Plosorejo. To overcome these obstacles by changing the execution time, if the weather is not friendly seen the implementation of extracurricular activities started earlier. In addition to utilizing classroom activities. The school principal must menggangarkan funds to purchase and provide the equipment necessary for extracurricular activities scout